Motivated Lamentations of Imam Hussein in modern Iraqi poetry (Journal of the College of Education for Women, 2019)
The Fountain of poetry Canot be suddenly flow or flood from emptiness. but it is streams and motives drive it to move . Forward tat Calmness and latent in depth of poet ,and try to Chang it in to high wives , go in to details inside the seas of poetry ,to sail threw it on the ships of poetry in creative styel to reach to the point from imaginary meaning , so every poet has direction to competein poetry poetsin Lament of Imam Hussain, There versification of poetry didn’t come from emptiness , but there was clashes motive them threw Calling the personality of Imam Hussain to learn lesson in avery beautiful and greative styel ,to be the expression poem from many sides in the personality of Imam Hussain from that events and facts that happen in that time , The poet discover and repyouduce the battle (Altaf) , Altaf battle whichis absent from ore eves but its never absent from our maind in present time .To specify this studing to detect the most important motives and clashes in lamentation of Imam Hussain , scince 1945 – 2010 , and out of coancern on that clashes to impact statement guide in lament of Imam Hussain , they have formend one of the pillars for the lamentation , to high light and constrat on to have it from researcher in modern eayes , Required research plant to divideol this study ing on three chapter , the first chapter concern on the intcnt function, the cecond chapter concern in conspt function while the third chapter concern in au thority function starting from couutinuation function of laurguage that mention by Gakbson .